The molecular mechanisms, roles, and potential applications of PANoptosis in cancer treatment - Ma, Wenyuan; Wang, Qiang; Guo, Lanfang; Ju, Xiaoli (Frontiers in Immunology, 2025)
PANoptosis, a newly identified form of programmed cell death regulated by the panoptosome complex, exhibits key characteristics of apoptosis, pyroptosis and necroptosis. It exerts a substantial influence on the initiation and progression of a spectrum of diseases, particularly in cancer, where its impact is increasingly being recognized. PANoptosis is closely related to tumorigenesis, carcinogenesis, metastasis, chemotherapy resistance, as well as the prediction of therapeutic responses and prognosis in cancer patients. In this review, we first review the discovery of PANoptosis and systematically analyze the composition of the panoptosome. Subsequently, we examine the role of PANoptosis in various types of cancer, encompassing its function within the tumor microenvironment, its role in tumor drug resistance, and its predictive role in cancer prognosis. Ultimately, we delve into strategies for targeting PANoptosis in cancer therapy, including targeting various molecules in the PANoptosis pathway, such as ZBP1, RIPK1, RIPK3, Caspases and other novel strategies like nanoinducers and viral vectors. This review aims to provide references and assistance for the research and application of PANoptosis in cancer treatment.